A nearby country called love - Abdoh, Salar (Viking, 2023)
"A sweeping, propulsive novel about the families we are born into and the families we make for ourselves, in which two brothers struggle to find their place in an Iran on the brink of combusting. Amid the alleyways of the Zamzam neighborhood of Tehran, a woman lights herself on fire in a desperate act of defiance, setting off a chain reaction of violence and protest. Haunted by the woman's death, Issa is forced to confront the contradictions within his own family as his brother Hashem, a prominent queer artist in Tehran's underground, defies their father, a skilled martial artist bound to traditional notions of honor and masculinity. Issa soon finds himself thrown into a circle of people living on the margins of a society at the brink of combusting, negotiating a razor-like code of conduct that rewards loyalty and encourages aggression and intolerance in equal measure. As the city explodes around him, Issa realizes that it is the little acts of kindness that matter most, the everyday humanity of individuals finding love and doing right by one another. Vibrant and evocative, intimate and intelligent, A Nearby Country Called Love is both a captivating window into contemporary Iran and a portrait of the parallel fates of a man and his country--a man who acknowledges the sullen and rumbling baggage of history but then chooses to step past its violent inheritance"--